2017
DOI: 10.1158/0008-5472.can-16-2755
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant SYK Kinase Signaling Is Essential for Tumorigenesis Induced by TSC2 Inactivation

Abstract: Somatic or germline mutations in the tuberous sclerosis complex (TSC) tumor suppressor genes are associated closely with the pathogenesis of lymphangioleiomyomatosis (LAM), a rare and progressive neoplastic disease that predominantly affects women in their childbearing years. Serum levels of the lymphangiogeneic growth factor VEGF-D are elevated significantly in LAM. However, there are gaps in knowledge regarding VEGF-D dysregulation and its cellular origin in LAM. Here we show that increased expression and ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 49 publications
5
17
0
1
Order By: Relevance
“…As expected, deregulated expression and activation of Syk was detected in TSC2-deficient cells and LAM lung lesions (56). Furthermore, Syk inhibitor fostamatinib reduced the proliferation of TSC2-deficient cells in vitro and suppressed TSC2-null xenograft tumor development in vivo (56). This study identified a Syk-dependent signaling inducing VEGF-D expression in peripheral blood mononuclear cells by monocyte chemoattractant protein (MCP)-1, which was elevated via signal transducer and activator of transcription (Stat3) signaling downstream of the mTORC1 signaling (56), demonstrating the strong therapeutic potential of Syk in LAM treatment.…”
Section: Receptor Tyrosine Kinases and Non-receptor Tyrosine Kinasessupporting
confidence: 82%
See 2 more Smart Citations
“…As expected, deregulated expression and activation of Syk was detected in TSC2-deficient cells and LAM lung lesions (56). Furthermore, Syk inhibitor fostamatinib reduced the proliferation of TSC2-deficient cells in vitro and suppressed TSC2-null xenograft tumor development in vivo (56). This study identified a Syk-dependent signaling inducing VEGF-D expression in peripheral blood mononuclear cells by monocyte chemoattractant protein (MCP)-1, which was elevated via signal transducer and activator of transcription (Stat3) signaling downstream of the mTORC1 signaling (56), demonstrating the strong therapeutic potential of Syk in LAM treatment.…”
Section: Receptor Tyrosine Kinases and Non-receptor Tyrosine Kinasessupporting
confidence: 82%
“…Hence, the hypothesis that Syk may be involved in LAM pathogenesis is worthy to be taken into consideration. As expected, deregulated expression and activation of Syk was detected in TSC2-deficient cells and LAM lung lesions (56). Furthermore, Syk inhibitor fostamatinib reduced the proliferation of TSC2-deficient cells in vitro and suppressed TSC2-null xenograft tumor development in vivo (56).…”
Section: Receptor Tyrosine Kinases and Non-receptor Tyrosine Kinasessupporting
confidence: 52%
See 1 more Smart Citation
“… 35 Another study demonstrated that Syk inhibition is a potential therapy for patients with LAM. 36 Recent research involving cells derived from patients with LAM showed that estrogen increased cell resistance to anoikis in vitro that was accompanied by a decreased accumulation of the proapoptotic protein, Bim, an activator of anoikis. Therefore, targeting Bim may be a plausible future treatment strategy for patients with LAM.…”
Section: Discussionmentioning
confidence: 99%
“…The study of peripheral blood in patients with LAM has previously identified multiple molecules 6 that are differentially present in the sera of women with LAM. The most important of these is vascular endothelial growth factor (VEGF)-D, a diagnostic biomarker of LAM in clinical use [7][8][9] and a candidate biomarker of therapeutic response to rapamycin. 10 To date, however, no large-scale studies of sera from women with LAM have been reported.…”
mentioning
confidence: 99%